2022
DOI: 10.3390/tomography8040148
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Acquisition Time and Improvement in Image Quality in T2-Weighted MR Imaging of Musculoskeletal Tumors of the Extremities Using a Novel Deep Learning-Based Reconstruction Technique in a Turbo Spin Echo (TSE) Sequence

Abstract: Background: The aim of this study was to assess the technical feasibility and the impact on image quality and acquisition time of a deep learning-accelerated fat-saturated T2-weighted turbo spin echo sequence in musculoskeletal imaging of the extremities. Methods: Twenty-three patients who underwent MRI of the extremities were prospectively included. Standard T2w turbo inversion recovery magnitude (TIRMStd) imaging was compared to a deep learning-accelerated T2w TSE (TSEDL) sequence. Image analysis of 23 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…These results are consistent with the literature, which showed a scan-time reduction for neuroradiological and non-neuroradiological applications [27][28][29][30][31][32]. Obtaining a consistently high image quality during the daily care of elderly, ill, and uncooperative patients can be a complex task.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with the literature, which showed a scan-time reduction for neuroradiological and non-neuroradiological applications [27][28][29][30][31][32]. Obtaining a consistently high image quality during the daily care of elderly, ill, and uncooperative patients can be a complex task.…”
Section: Discussionsupporting
confidence: 91%
“…The combination of these sequences with quantitative T2 sequences might improve the detection of beginning histopathological changes even further than each of these techniques alone. The recently reported reduction in acquisition time using deep-learning-based reconstruction techniques in T2-weighted MR imaging may further enhance this advantage by allowing for the acquisition of additional information without negatively impacting the clinical workflow [41].…”
Section: Discussionmentioning
confidence: 99%
“…DL could also be used to correctly classify breast lesions detected on an X-ray mammography to reduce the false positive recall rate and improve the efficacy of breast cancer screening [2]. Park et al [3] showed that radiomics features of ductal carcinoma in situ on breast MR imaging may predict ipsilateral tumoral recurrence, while DL-accelerated MR imaging may improve image quality in MR images of musculoskeletal tumors [4]. AI could also be implemented in imaging reconstruction and automatic diagnoses to reduce radiologist workloads.…”
mentioning
confidence: 99%